2

Sequences and series

We will first deal with sequences, and then study infinite series in terms of the associated sequence of partial sums.

2.1

Sequences

By a sequence, we will mean a collection of numbers a1 , a2 , a3 , . . . , an , an+1 , . . . , which is indexed by the set N of natural numbers. We will often denote it simply as {an }. 1 A simple example to keep in mind is given by an = n , which appears to decrease towards zero as n gets larger and larger. In this case we would like to have 0 declared as the limit of the sequence. A quick example of a sequence which does not tend to any limit is given by the sequence {1, −1, 1, −1, . . . }, because it just oscillates between two values; for this sequence, an = (−1)n+1 , which is certainly bounded. Definition 2.1 A sequence {an } is said to converge, i.e., have a limit A, iff for any ε > 0 there exists N = N (ε) > 0 s.t. for all n ≥ N we have |an − A| < ε. Notation: limn→∞ an = A, or an → A as n → ∞. Two Remarks: (i) It is immediate from the definition that for a sequence {an } to converge, it is necessary that it be bounded. However, it is not sufficient, i.e., {an } could be bounded without being convergent. Indeed, look at the example an = (−1)n+1 considered above. (ii) It is only the tail of the sequence which matters for convergence. Otherwise put, we can throw away any number of the terms of the sequence occurring at the beginning without upsetting whether or not the later terms bunch up near a limit point.

Lemma 2.2 If limn→∞ an = A and limn→∞ bn = B, then 1

1) limn→∞ (an + bn ) = A + B 2) limn→∞ (can ) = cA, for any c ∈ R 3) limn→∞ an bn = AB 4) limn→∞ an /bn = A/B, if B ̸= 0. Proof of 1) For any ε > 0, choose N1 and N2 so that for n1 ≥ N1 , n2 ≥ N2 , |an1 − A| < ε/2, |bn − B| < ε/2. Then for n ≥ max{N1 , N2 }, we have ε ε |an + bn − A − B| < 2 + 2 = ε. Hence A + B is the limit of an + bn as n → ∞. 2 Proofs of the remaining three assertions are similar. For the last one, note that since {bn } converges to a non-zero number B, eventually all the terms bn will necessarily be non-zero, as they will be very close to B. So, in the sequence an /bn , we will just throw away some of the initial terms when bn = 0, which doesn’t affect the limit as the bn occurring in the tail will all be non-zero. 2
1 Example: We have limn→∞ n = 0. Indeed, given ε > 0, we may choose 1 an N ∈ N such that ∃N > ε , because N is unbounded. This implies that for 1 1 1 n ≥ N , we have | n − 0| ≤ N < ε. Hence { n } converges to 0. 2

Definition A sequence is said to be monotone increasing, denoted an ↗, if an+1 ≥ an for all n ≥ 1, and monotone decreasing, denoted an ↘, if an+1 ≤ an for n ≥ 1. We say {an } is monotone (or monotonic) if it is of one of these two types. Theorem 2.3 A bounded, monotonic sequence converges. Proof. Assume bounded and an ↗. Let A = sup{an }. (We write sup for supremum, which is the same as the least upper bound, and inf for infimum, which is the greatest lower bound.) For any ε > 0, A − ε is not an upper bound ⇒ ∃aN > A − ε. But an ≥ aN for n ≥ N ⇒ −ε < an − A ≤ 0 for all n ≥ N . Hence {an } converges with limit A. If {an } is (bounded and) monotone decreasing, then look at {bn }, with bn = −an . Then this new sequence is monotone increasing and has a limit B, which is the sup of {bn }. Then A = −B is the inf of {an }, and an → A as n → ∞. 2

2 Example: limn→∞ 21 = 0. Indeed, the sequence is bounded and monon tone decreasing, hence ∃A such that limn→∞ 1/2n = A. Note that if we multiply the terms of the sequence by 2, then this new sequence also converges to A. On the other hand, by Lemma 1.2, part 2), this limit should be 2A. Then 2A = A, implying that A = 0. 2 This example is a special case of a more general phenomenon: Lemma 2.4 Let y be a positive real number. Then {y n } is unbounded if y > 1, while lim y n = 0 if y < 1.
n→∞

Proof of Lemma. Suppose y > 1. Write y = 1 + t with t > 0. Then by the binomial theorem (which can be proved by induction), n ∑ (n ) n n y = (1 + t) = tk , k
k=0

which is ≥ 1 + nt (as t > 0). Since 1 + nt is unbounded, i.e, larger than any number for a big enough n, y n is also unbounded. Now let y < 1. Then y −1 is > 1 and hence {y −n } is unbounded. This implies that, for any ϵ > 0, y n is < ϵ for large enough n. Hence the sequence y n converges to 0. 2 As an exercise, try to extend this Lemma and prove that for any y ∈ R with |y| < 1, the sequence {y n } converges to 0. Here is an example. Define a sequence {sn } by putting sn = 1 + 1 1 1 + + ... + . 1! 2! (n − 1)!

It is not hard to see that this sequence is bounded. Try to give a proof. (In fact one can show that it is bounded by 3, but we do not need the best possible bound at this point.) Clearly, sn+1 > sn , so the sequence is also monotone increasing. So we may apply Theorem 1.3 above and conclude that it converges to a limit e, say, in R. But it should be remarked that one can show with more work that e is irrational. So there is a valuable lesson to be learned here. Even though {an } is a bounded, monotone sequence of rational numbers, there is no limit in Q; one has to go to the enlarged number system R. 3

2.2

The Squeeze Principle

An efficient way to prove the convergence of a sequence is to see if it can be squeezed between two other sequences which converge to the same limit. Proposition 1 Suppose {an }, {bn }, {cn } are sequences of real numbers such that bn ≤ an ≤ cn , ∀ n ≥ 1. Suppose moreover that the sequences {bn } and {cn } are convergent with the same limit L, say. Then the sequence {an } converges as well, with
n→∞

lim an = L.

Example: For any fixed real number x, consider the sequence {an }, with an = sin(nx) . Then, since sin(nx) takes values between −1 and 1, the hypothen ses of the Proposition are satisfied if we take bn = −1/n and cn = 1/n, since an and bn both converge to zero. We conclude that { sin(nx) } also converges n to 0, regardless of what x is. Before giving a proof of Proposition 1, let us note the following useful consequence for sequences {an } with non-negative terms, by taking bn = 0 for all n. Corollary 2.5 Suppose {an }, {cn } are sequences of non-negative real numbers, with {cn } convergent, such that an ≤ cn , ∀ n ≥ 1, and
n→∞

lim cn = 0.

Then the sequence {an } converges as well, with
n→∞

lim an = 0..

4

Proof of Proposition 1. Pick any ε > 0. Then, the convergence of {bn }, resp. {cn }, implies that we can find some N1 > 0, resp. N2 > 0, such that for all n ≥ N1 , resp. n ≥ N2 , |L − bn | < ε, resp. |L − cn | < ε.

Put N = max(N1 , N2 ). Then for all n ≥ N , the fact that an is squeezed between bn and cn implies that |L − an | < ε. Since ε was arbitrary, this shows the sequence {an } converges to the same limit L. 2

2.3

Cauchy’s criterion

The main problem with the definition of convergence of a sequence is that it is hard to verify it. For instance we need to have a candidate for the limit to verify the condition for convergence. One wants a better way to check for convergence. As seen above, boundedness is a necessary, but not sufficient, condition, unless the sequence is also monotone. Is there a necessary and sufficient condition? A nineteenth century French mathematician named Augustin-Louis Cauchy gave an affirmative answer. (His criterion also works for sequences of complex numbers.) A sequence {an } is said to be a Cauchy sequence iff we can find, for every positive ϵ, an N > 0 such that (2.2.1) |am − an | < ϵ whenever n, m > N.

This is nice because it does not mention any limit. Lemma 2.6 Every convergent sequence is Cauchy. Proof. Suppose an → L. Pick any ϵ > 0. Then by definition, we can find an N > 0 such that for all n > N , we have |L − an | < 5 ϵ . 2

Then for n, m > N , the triangle inequality gives |am − an | ≤ |am − L| + |L − an | < ϵ ϵ + = ϵ. 2 2 2 Here comes the beautiful result of Cauchy, which we just state without proof: Theorem 2.7 Every Cauchy sequence of real (resp. complex) numbers converges in R (resp. C). One can use Cauchy sequences to give a construction of R. (A description of this, as well as a proof of Cauchy’s theorem will be in the expanded Notes, which interested students could look up.)

2.4

∑ Definition 2.8 A series ∞ ak converges if the sequence of partial sums k=1 s1 = a1 , s2 = a1 + a2 , s3 = a1 + a2 + a3 , . . . converges.
∞ ∑ k=1

Series: Basic Notions

sk = lim (a1 + · · · + an )
n→∞

Note that, as seen with sequences, the convergence/divergence of a series does not depend on the first finitely many terms; it depends only on the “tail”. Example: We have
∞ ∑ k=0

xk =

1 , 1−x

for |x| < 1.

∑ Indeed n xk = k=0 the previous example.

1−xn+1 , 1−x

and xn+1 → 0 as n → ∞ by the argument of

∑ ∑ ∑ Lemma 2.9 If an and bn converge then (αan + βbn ) also converges for any α, β ∈ R. 6

This is a consequence of Lemma 2.2 and Definition 2.7. ∑ 1 Example: The harmonic series ∞ n diverges. Indeed, note that n=1 ∑2n 1 1 1 k=n+1 k > n · 2n = 2 . Thus
2S 2 4 8 2S the sequence of ∑1 ∑ ∑ ∑ ∑ S = + + +··· + > ⇒ partial sums n 2 n=1 1 3 5 is unbounded. 2S−1

∑ 1 For the same reason ∞ n+1 diverges, since it is the same series without n=1 the first term. ∑ ∑ 1 1 1 What about ∞ ( n − n+1 ) = ∞ n(n+1) ? n=1 n=1 Look at the partial sums sn =
n ∑ n=1 1 k(k+1) 1 1 = (1 − 1 ) + ( 2 − 1 ) + · · · + ( n − 2 3 1 ) n+1

=1−

1 . n+1

This is an example of a telescoping series ∑ an with an = bn − bn+1

n = 1, 2, . . .

∑ Then if ∃ limn→∞ Bn = b0 then an = b 1 − b 0 . ∑∞ Question: Is the series n=1 (−1)n convergent? Hope you can figure this out yourself.

2.5

Tests for convergence of series
∑∞
n=1

Proposition 2 If

an converges, then limn→∞ an = 0.

Proof. Since sn = (a1 + · · · + an ) goes to a limit L as n → ∞, then the same is true of sn−1 , and since an = sn − sn−1 , we must have an → L − L = 0. 2 This is a necessary condition. Theorem 2.10 Assume that an ≥ 0 for any n ≥ 1. Then the series converges if and only if the sequence of its partial sums is bounded. 7 ∑ an

Proof The sequence of partial sums sn is monotone increasing because an = sn − sn−1 is non-negative. We know that convergence implies boundedness. Conversely, if the monotonic sequence {sn } is bounded, it is convergent by Theorem 2.3. 2 ∑∞ ∑n k−1 Example: , and k=1 1/2k−1 ≤ k=0 1/k! converges. Indeed, 1/k! ≤ 1/2 ∑∞ k−1 = 2. This limit is denoted by e; we saw it earlier. k=1 1/2 The Comparison test Assume an ≥ 0 and bn ≥ 0 for all n ≥ 1. If there exists a positive constant C such that an ≤ cbn for all n ≥ 1 then ∑ ∑ convergence of bn implies convergence of an . ∑n ∑n Proof. 2 k=1 ak ≤ c · k=1 bn . Limit comparison test: Assume an > 0 and bn > 0 for all n ≥ 1, and ∑ ∑ suppose that limn→∞ an /bn = 1. Then an converges if and only if bn converges.
n Proof. ∃N ∈ N such that for all n ≥ N , 1/2 < an < 3/2 ⇒ bn < 2an b 2 and an < 3 bn . Since the convergence does not depend on finitely many first terms, the result follows by applying the comparison test. 2 ∑ 1 ∑ 1 Example: converges. Indeed, we showed before that n2 n(n+1)

converges, and limn→∞

n(n+1) n2

= limn→∞ ∑∞

1 (1+ ) n 1

= 1.

2

Theorem 2.11 (Root test). Let 1/n such that an → R as n → ∞.

n=1

an be a series of nonnegative terms

(a) If R < 1, the series converges. (b) If R > 1, the series diverges. (c) If R = 1, the test is inconclusive. Proof. Assume R < 1 and choose x ∑ < x < 1. Then 0 ≤ an ≤ x is :R satisfied for n ≥ N . Hence, an ≤ xn , and an < ∞ by the comparison test. If R > 1, then an > 1 for infinitely many n, which implies an ̸→ 0.Hence the series diverges. 2 ∑1 ∑ 1 For R = 1 we have two examples: and . n n2 ∑ Example: n/3n < ∞. 8
1/n

∑ Theorem 2.12 (Ratio test) Let ∞ an be a series of positive terms such n=1 that an+1 → L as n → ∞. an (a) If L < 1, the series converges. (b) If L > 1, the series diverges, (c) If L = 1, the test is inconclusive. Proof. Assume L < 1 and choose x : L < x < 1. Then an+1 < x for all an n ≥ N . This implies an+1 an < n for all n ≥ N. n+1 x x a n Thus, the sequence an /x ↘ for n ≥ N ⇒ xn ≤ const. Now the comparison n test proves (a). (b) follows from the fact that an is not decreasing. ∑1 ∑ 1 (c) same 2 examples , . 2 n n2 ∑ 2n n n+1 2 2 Example: converges. Indeed, 2 / (n+1)! = (n+1)! → 0. n! n!

2.6

Absolute and Conditional Convergence

Now let us consider series some of whose terms may be negative. ∑∞ ∑∞ Proposition 3 n=1 an is convergent if n=1 |an | is convergent. ∑ Proof. Let us prove that bn with bn = an + |an | converges. We have ∑ bn = 0 or bn = 2|an |. Hence bn ≤ 2|an |, and by comparison test bn < ∞. Since an = bn − |an |, we are done. 2 ∑ Definition 2.13 A series an is said to be absolutely convergent if ∑ ∑ ∑ ∑ |an | converges. If an converges and |an | diverges then an is said to be conditionally convergent. Theorem 2.14 (Leibniz) If {an } is ∑ monotonic decreasing sequence with a limit 0, then the alternating series (−1)n−1 an converges. If S is its sum and sn is its nth partial sum then 0 < |S − sn | < an+1 for all n ≥ 1. 9 The converse is not true.

Proof The partial sums s2n is monotone increasing because s2n+2 − s2n = a2n+1 − a2n+2 > 0. By a similar argument, s2n−1 ↘. Both sequences are bounded from below by s2 and from above by s1 . Denote S ′ = limn→∞ s2n , S ′ = limn→∞ s2n−1 . Then S ′ − S ′′ = lim(s2n − s2n−1 ) = ∑ lim(−a2n ) = 0 ⇒ S ′ = S ′′ . Hence, the series an converges and its sum is ′ ′′ S = S = S . Further, 0 < S − s2n ≤ s2n+1 − s2n = a2n+1 , 0 < s2n−1 − S ≤ s2n−1 − s2n = a2n . Example: Example: ∑ (−1)n /n is conditionally convergent. (James Gregory 1672, Gottfried Wilhelm Leibniz 1673)
π 4 1 = 1 − 1 + 5 − 1 + ··· + 3 7 (−1)n−1 2n−1

2

+ ....

This gives a very slowly convergent approximation for π by cutting off the tail at some large enough N . Leibniz was a founder of Optimism: “Our universe is the best possible one God could have made.” Some think incorrectly that he was mocked by Voltaire for this philosophy in Candide.

2.7

Power Series
∞ ∑ n=0

Definition 2.15 A power series is an infinite series of the form an (z − a)n = a0 + (z − a)a1 + (z − a)2 a2 + . . .

∑ Proposition 4 Assume that the power series an z n converges for a particular z ̸= 0, say for z = z1 . Then the series converges absolutely for every z with |z| < |z1 |. ∑ n n n Proof. Since an z1 converges, an z1 → 0 ⇒ |an z1 | < 1 for n ≥ N . If |z| < |z1 | then zn z for n ≥ N ≤ n z1 z1 ∑ z n ∑ Since | z1 | < ∞, by the comparison test, an z n converges.
n |an z n | = |an z1 | n

2

10

∑ Theorem 2.16 Assume that the power series an z n converges for at least one z ̸= 0, say z = z1 , and that it diverges for at least one z, say z = z2 . Then there exists a positive real number ρ, called the radius of convergence, such that the series converges absolutely if |z| < r and diverges if |z| > r. ∑ Proof. Denote by A the set of positive z for which an z n converge. We know that A ̸= ∅ and A∑ |z2 |. Set r = sup A. If |z| < r then there ≤ exists x ∈ (|z|, r) such that an xn converges ⇒ by the previous theorem ∑ n an z absolutely converges. 2 ∑ zn Example: S := . Its radius of convergence is 1. Thus S converges n whenever |z| < 1 and diverges when |z| > 1. It is tricky understand what happens when |z| = 1. If z ∈ R, then we are reduced to consider exactly two boundary cases, i.e., when ρ = 1, which ∑ 1 are (i) ∑ harmonic series ∞ n , which diverges, and (ii) the alternating the n=1 ∞ 1 series n=1 (−1)n n , which converges by Leinbniz. So both situations can occur at the radius of convergence. The problem gets even more interesting if we allow z to be a complex number. Then z = eiθ for some angle θ ∈ R (which can be taken to be between 0 and 2π (with 0 included), and by de Moivre’s theorem, z n = einθ = cos(nθ) + i sin(nθ). Consequently, the series splits up into a sum of two infinite series:
∞ ∞ ∞ ∑ zn ∑ cos(nθ) ∑ sin(nθ) S= = +i . n n n n=1 n=1 n=1

When θ = 0, the first part, called the real part of S, is the harmonic series (which diverges), and the second part, said to be (i times) the imaginary part of S, is zero. It turns out that for any θ strictly between 0 and 2π, S converges.

11

Sign up to vote on this title
UsefulNot useful